Macroeconomic Antecedents of Stock Returns and Exchange Rate - Bhanumurthy, K. V.; Singh, Amit Kumar; Aggarwal, Annu (Indian Journal of Finance, 2019)
This study attempted to empirically test the trend and behaviour of macroeconomic variables, that is, money supply, interest rate, inflation rate, GDP, stock returns, and exchange rates during different policy periods classified as liberalization, globalization, world recovery, and global financial crisis in India over the period from April 1991 to March 2015 by using dummy variable : structural growth equation both for intercept and slope. These macroeconomic antecedents surround the relationship between stock returns and exchange rates ; although, these macroeconomic antecedents may not be the direct determinants of foreign exchange rates and stock returns. It was observed that all the four global policy periods had a statistically significant impact sometimes on the levels and sometimes on the growth rate of the macroeconomic antecedents under study.